A preparation method of Ni3(HITP)2 / Mxene heterostructure and ethanol sensor

Through template-assisted growth technology and the conductive characteristics of MXene nanosheets, Ni3 (HITP)2/MXene composite layered material was prepared, which solved the problems of poor conductivity of MOF-based gas sensors and poor solution processability, and achieved high sensitivity and high selectivity gas sensing effect.

CN117228736BActive Publication Date: 2025-05-02XI AN JIAOTONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310583388.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-22
Publication Date
2025-05-02
Estimated Expiration
2043-05-22

AI Technical Summary

Technical Problem

The existing MOF-based gas sensors have problems such as poor conductivity and poor solution processability, which limits their wide application in the fields of resistive sensor parts and gas sensors.

Method used

Through template-assisted growth technology and the excellent conductivity of MXene nanosheets, controllable self-assembly of Ni3 (HITP)2 is achieved, and ultra-thin, good dispersibility and high conductivity Ni3 (HITP)2/MXene composite layered material is prepared.

Benefits of technology

The resistance response and sensitivity of Ni3 (HITP)2 to a variety of organic gases are improved, the film making process of MOF materials is simplified, the performance of gas sensors is enhanced, and the problem of poor solution processability of MOF materials is overcome.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117228736B_ABST
    Figure CN117228736B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method of Ni3(HITP)2 / MXene heterostructure and an ethanol sensor. Specifically, HITP·6HCl is dissolved in ethanol to obtain a HITP·6HCl solution, and then concentrated ammonia water and nickel nitrate solution are added to the HITP·6HCl solution to obtain a mixed solution; MXene nanosheet dispersion is added to the mixed solution, and ultrasonic treatment is carried out to obtain a uniform solution, and the above mixed solution is heated for in-situ growth to obtain a Ni3(HITP)2 / MXene composite nanosheet suspension. By utilizing the two-dimensional nanosheet characteristics of the Ni3(HITP)2 / MXene heterostructure, its dispersibility is greatly improved, making it extremely easy to prepare a uniform and dense large-area film during solution processing. This method successfully prepares Ni3(HITP)2 / MXene composite nanosheets with excellent solution processability, overcoming the inherent problem of the lack of solution processability of MOF materials. In view of the excellent solution processability of the Ni3(HITP)2 / MXene heterostructure, it is convenient to prepare Ni3(HITP)2 / MXene-based gas sensors; the prepared Ni3(HITP)2 / MXene-based sensors have excellent sensing characteristics, such as high selectivity and high sensitivity to ethanol, and detection at room temperature, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of semiconductor sensors and relates to a preparation method of a Ni3(HITP)2 / MXene heterostructure and an ethanol sensor. Background Art

[0002] Ethanol has very important uses in monitoring drunk driving, food packaging safety testing, fermentation process control, and detecting potential leaks in chemical plants. However, due to its inherent flammability and other dangerous properties, high-precision real-time monitoring is particularly important during the development, storage, transportation and use of ethanol.

[0003] Metal-organic frameworks (MOFs) are a novel class of porous materials typically formed by the coordination bonding of metal clusters and organic ligands. Due to their high porosity, large specific surface area, tunable pore size / shape, and host-guest interactions, they exhibit broad application prospects in gas adsorption / separation, adsorption, heterogeneous catalysis, chemical sensing, drug delivery, and nonlinear optics. Thanks to their high surface area, tunable pore size, and host-guest interactions, MOFs can selectively enrich specific gases, significantly improving the sensitivity and selectivity of gas detection. The preparation and application of MOF-based gas sensors have also been extensively studied. However, major challenges remain: First, most MOFs have poor intrinsic conductivity, and the variety of semiconducting MOFs is limited. The question of how to achieve coupling with MOFs through second-phase interfaces or create heterojunctions to improve the electrical and sensing properties of MOFs at the electronic structural level is promising for their widespread application in resistive sensors. Second, MOFs inherently lack solution processability due to their extended topological network structure and crystallinity, resulting in poor film-forming properties, which limits their widespread application in the field of gas sensors.

[0004] The key to overcoming its poor solution processability is to overcome strategic innovations to prevent or slow down its stacking due to inter-particle or inter-layer van der Waals forces. These issues have greatly limited the mass production and application of high-performance MOF-based gas sensors, and therefore it is urgent to overcome these key challenges.

[0005] By leveraging template-assisted growth techniques and the excellent conductive properties of MXene nanosheets, researchers are able to achieve controlled self-assembly of Ni3(HITP)2, resulting in an ultrathin, well-dispersed, and highly conductive Ni3(HITP)2 / MXene composite layered material. This approach is expected to address these challenges and enable the mass production of high-performance gas sensors. Summary of the Invention

[0006] The purpose of the present invention is to solve the problems in the prior art and provide a preparation method of Ni3(HITP)2 / MXene heterostructure and an ethanol sensor.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A method for preparing a Ni3(HITP)2 / MXene heterostructure comprises the following steps:

[0009] S1: dissolving HITP·6HCl in ethanol to obtain a HITP·6HCl solution, and then adding concentrated ammonia water and nickel nitrate solution to the HITP·6HCl solution to obtain a mixed solution;

[0010] S2: Add MXene nanosheet dispersion to the mixed solution, then ultrasonicate and heat the mixed solution to obtain Ni3(HITP)2 / MXene composite nanosheet suspension in situ.

[0011] A further improvement of the present invention is:

[0012] In step S1, the preparation of the nickel nitrate solution includes adding nickel nitrate hexahydrate to ethanol and performing ultrasonic treatment to obtain the nickel nitrate solution.

[0013] In step S1, the molar ratio of the nickel nitrate solution to the HITP·6HCl solution is (3-2):(3.5-2).

[0014] In step S1, the amount of concentrated ammonia solution used is 0.3-0.5 mL.

[0015] In the step S1, the ratio of nickel nitrate hexahydrate to ethanol is 0.028-0.032 mmol: 5-6 mL.

[0016] In the step S1, the ratio of HITP·6HCl to ethanol is 0.019-0.022 mmol: 5-6 mL.

[0017] In step S2, the heating temperature is 55-65° C. and the heating time is 4-6 hours.

[0018] In step S2, the centrifugation time is 1-3 minutes;

[0019] After centrifugation, the solution is washed for 5 or more times.

[0020] An ethanol gas sensor comprises a Ni3(HITP)2 / MXene composite nanosheet suspension obtained by the preparation method of the present invention, wherein the Ni3(HITP)2 / MXene composite nanosheet suspension is loaded on the surface of the sensor.

[0021] The thickness of the Ni3(HITP)2 / MXene layer is 220-450 nm.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention discloses a method for preparing a Ni3(HITP)2 / MXene heterostructure, wherein an ethanol-sensitive material Ni3(HITP)2 is in situ grown on the surface of a template layer MXene nanosheet to prepare a Ni3(HITP)2 / MXene composite structure, and the high conductivity of the bottom template MXene nanosheet is utilized to enhance the conductivity of the Ni3(HITP)2 / MXene composite structure, thereby improving the resistance response and sensitivity of Ni3(HITP)2 to various organic gases (VOCs); and utilizing the two-dimensional nanosheet characteristics of the Ni3(HITP)2 / MXene heterostructure, the ethanol-sensitive material Ni3(HITP)2 is in situ grown on the surface of a template layer MXene nanosheet to prepare a Ni3(HITP)2 / MXene composite structure. The dispersibility of the dispersion makes it extremely easy to prepare uniform and dense large-area thin films during solution processing, further reducing the difficulty of forming MOF materials on the device surface and significantly simplifying the film-making process of MOF materials as the sensing layer in gas sensor devices. At the same time, the synergistic effect of the heterojunction between Ni3(HITP)2 / MXene effectively increases the overall specific surface area, providing more active sites, allowing it to adsorb more gas and enhance the effective combination of gas and the central main group element Ni, effectively enhancing the response performance of Ni3(HITP)2 / MXene and overcoming the inherent lack of solution processability of MOF materials.

[0024] The present invention discloses an ethanol gas sensor. A Ni3(HITP)2 / MXene structure is loaded on the sensor surface, which has stronger anti-interference ability and shows better selectivity and higher sensitivity to ethanol. The obtained Ni3(HITP)2 / MXene-based sensor has excellent sensing characteristics and improves the performance of the sensor. The synergistic effect of the heterojunction between Ni3(HITP)2 / MXene can reduce the activation energy of the reaction of ethanol on the MOF surface, promote the reaction of ethanol with the central main group element Ni, and regulate the electron transfer mechanism, showing selectivity for ethanol gas, thereby developing a composite material ethanol gas sensor with both high selectivity and high sensitivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without paying any creative work.

[0026] Figure 1 3 are microscope images of the material prepared in Example 1 of the present invention (where a represents a scanning electron microscope image of Ni3(HITP)2; b represents a scanning electron microscope image of Ni3(HITP)2 / MXene nanosheets; c and d both represent atomic force microscope images of Ni3(HITP)2 / MXene nanosheets);

[0027] Figure 2 This is an image analysis of the Ni3(HITP)2 / MXene nanosheets prepared in Example 1 of the present invention (wherein, a and b represent transmission electron micrographs of Ni3(HITP)2 / MXene nanosheets, and c to e represent elemental mapping under a transmission electron microscope);

[0028] Figure 3 is the XRD pattern of Ni3(HITP)2 and Ni3(HITP)2 / MXene nanosheets prepared in Example 1;

[0029] Figure 4 2 are the conductivity test graphs of Ni3(HITP)2 and Ni3(HITP)2 / MXene nanosheets prepared in Example 1 (where a represents the resistivity curve and b represents the conductivity curve);

[0030] Figure 5 The obtained components are in response to ethanol gas (wherein, a represents the response of Ni3(HITP)2 / MXene nanosheets prepared in Example 1 of the present invention to 0.1-1.5 ppm ethanol gas; b represents the response of Ni3(HITP)2 / MXene nanosheets to 1-10 ppm ethanol gas; c represents the response of Ni3(HITP)2 to 1-10 ppm ethanol gas);

[0031] Figure 6 The selective responses of Ni3(HITP)2 and Ni3(HITP)2 / MXene nanosheets prepared in Example 1 of the present invention to different gases (where a represents the selective response of Ni3(HITP)2 to different gases; b represents the selective response of Ni3(HITP)2 / MXene nanosheets to different gases). DETAILED DESCRIPTION

[0032] To make the objectives, technical solutions, and advantages of the embodiments of the present invention more clear, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings herein can be arranged and designed in various different configurations.

[0033] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention as claimed, but rather merely represents selected embodiments of the present invention. All other embodiments derived by persons of ordinary skill in the art based on the embodiments of the present invention without creative effort shall fall within the scope of protection of the present invention.

[0034] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, it does not need to be further defined or explained in subsequent drawings.

[0035] In the description of the embodiments of the present invention, it should be noted that if the terms "upper," "lower," "horizontal," "inner," etc. appear, the orientation or positional relationship indicated is based on the orientation or positional relationship shown in the accompanying drawings, or the orientation or positional relationship in which the inventive product is typically placed when in use. These terms are merely for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or component referred to must have a specific orientation, be constructed, or operate in a specific orientation. Therefore, they should not be construed as limitations on the present invention. In addition, the terms "first," "second," etc. are used only to distinguish descriptions and should not be construed as indicating or implying relative importance.

[0036] In addition, if the term "horizontal" appears, it does not mean that the component must be absolutely horizontal, but can be slightly tilted. For example, "horizontal" only means that its direction is more horizontal than "vertical", and does not mean that the structure must be completely horizontal, but can be slightly tilted.

[0037] In the description of the embodiments of the present invention, it should be noted that, unless otherwise expressly specified or limited, the terms "disposed," "installed," "connected," and "connected" should be understood in a broad sense. For example, they can refer to fixed connections, detachable connections, or integral connections; they can refer to mechanical connections or electrical connections; they can refer to direct connections or indirect connections through an intermediate medium; and they can refer to internal connections between two components. Those skilled in the art will understand the specific meanings of the above terms in the present invention based on specific circumstances.

[0038] The present invention is described in further detail below with reference to the accompanying drawings:

[0039] See also Figure 1The present invention discloses a method for preparing a Ni3(HITP)2 / MXene heterostructure. By utilizing the template effect of two-dimensional MXene nanosheets and their lattice matching with Ni3(HITP)2, the controlled self-assembly of Ni3(HITP)2 on the surface is achieved, resulting in an ultrathin, well-dispersed Ni3(HITP)2 / MXene composite layered material. The unique electronic coupling effect and heterogeneous synergistic effects of Ni3(HITP)2 / MXene endow the Ni3(HITP)2 / MXene-based sensor with excellent sensitivity (ppb level) and specificity for ethanol vapor.

[0040] The specific steps include:

[0041] Step 1. Nickel nitrate hexahydrate (Ni(NO3)2·6H2O) (0.028-0.032 mmol) is added to ethanol and ultrasonically treated to obtain a nickel nitrate solution. HITP·6HCl is then dissolved in ethanol (3.8-4.0 mmol / L) and ultrasonically treated to obtain a HITP·6HCl solution. Subsequently, concentrated ammonia solution (NH3·H2O) and the nickel nitrate solution are added dropwise to the HITP·6HCl solution to obtain a mixed solution.

[0042] Furthermore, in step S1, the molar ratio of the nickel nitrate solution and the HITP·6HCl solution is 3:2-3.5:2, and the amount of concentrated ammonia solution (NH3·H2O) added is 0.3-0.5 mL;

[0043] Furthermore, in step S1, 5-6 mL of ethanol was added for every 0.028-0.032 mmol of Ni(NO3)2·6H2O, and 5-6 mL of ethanol was added for every 0.019-0.022 mmol of HITP·6HCl;

[0044] Step 2. Take the MXene nanosheet dispersion and add it to the mixed solution prepared in step S1. The mixed solution is ultrasonically treated (15-20 minutes). After the ultrasonic treatment, the mixed solution is placed in a reactor and heated (55-65°C). After reacting for 4-6 hours, the obtained black suspension is centrifuged and washed multiple times to finally obtain a uniformly dispersed Ni3(HITP)2 / MXene composite nanosheet suspension.

[0045] Furthermore, in step S2, the amount of MXene nanosheet dispersion added is 3-5 mL;

[0046] Furthermore, in step S2, the power of the water bath ultrasound is 200-300W, and the cumulative ultrasound time is 15-20 minutes.

[0047] Furthermore, in step S2, the oven heating temperature is 55-65° C., and the heating time is 4-6 hours.

[0048] Furthermore, in step S2, the centrifugal speed is 8000-10000 r / min, the centrifugal time is 1-2 min, and the centrifugal washing operation is performed at least 5 times;

[0049] The present invention also discloses an ethanol sensor, wherein a Ni3(HITP)2 / MXene composite nanosheet suspension is loaded on the sensor surface. The specific preparation process is as follows:

[0050] The prepared Ni3(HITP)2 / MXene nanosheet dispersion was evenly spin-coated or drop-coated on the surface of the sensor printed with interdigital electrodes. The entire sensor was then heated and dried at 80°C. After it was completely dry, gas sensing tests were performed.

[0051] The amount of the Ni3(HITP)2 / MXene composite nanosheet dispersion is 0.2-0.3 mmol / L;

[0052] The thickness of the Ni3(HITP)2 / MXene layer is 220-450 nm;

[0053] Furthermore, the obtained sensor test electrodes are connected to the electrode columns of the octagonal base located in the detection cavity to obtain an ethanol gas sensor with Ni3(HITP)2 / MXene as the sensitive material.

[0054] The present invention also discloses a method for testing an ethanol gas sensor:

[0055] After sealing the detection chamber, introduce sufficient N2 until the baseline resistance is stable. Then introduce ethanol gas with different concentrations in the range of 0.1-10ppm and observe the resistance response as the gas content changes.

[0056] Example 1

[0057] Step 1: Prepare the mixture:

[0058] 0.028 mmol of nickel nitrate hexahydrate (Ni(NO3)2·6H2O) was added to 5 mL of ethanol and ultrasonically treated to obtain a nickel nitrate solution. 0.020 mmol of HITP·6HCl was then dissolved in 5 mL of ethanol and ultrasonically treated to obtain a HITP·6HCl solution. Subsequently, 0.3 ml of concentrated ammonia solution (NH3·H2O) and the obtained nickel nitrate solution were added dropwise to the HITP·6HCl solution to obtain a mixed solution.

[0059] Step 2: Preparation of Ni3(HITP)2 / MXene nanosheets

[0060] 3 mL of MXene nanosheet dispersion was added to the mixed solution prepared in step 1, and the mixed solution was subjected to water bath sonication. After the sonication, the mixed solution was placed in a reactor for heating reaction. The oven heating temperature was 55°C and the heating time was 4 hours. After the reaction, the obtained black suspension was centrifuged and washed at a centrifugal speed of 8000 r / min and a centrifugal time of about 1 minute. The number of centrifugal washes was 5 times.

[0061] Furthermore, the washed black suspension is dried under vacuum at 150°C to obtain Ni3(HITP)2 / MXene, or ethanol is added to the washed black suspension to prepare a Ni3(HITP)2 / MXene dispersion with a certain concentration.

[0062] Step 3: Device Pretreatment

[0063] The sensor device printed with interdigital electrodes was immersed in ethanol for 1 day to fully remove impurities on the surface of the sensor device, and then heated to 80°C for drying.

[0064] Step 4: Prepare the sensing layer

[0065] The prepared Ni3(HITP)2 / MXene dispersion was evenly spin-coated or drop-coated on the surface of the sensor printed with interdigital electrodes. The entire sensor was then heated and dried at 80°C. After it was completely dry, a gas sensing test was performed, and the thickness of the entire sensing layer was controlled at 220nm.

[0066] Step 5: Sensor Assembly

[0067] The test electrodes of the sensor prepared by the above steps are connected to the electrode columns located at the octagonal base of the detection cavity, thereby obtaining an ethanol gas sensor with Ni3(HITP)2 / MXene as the sensitive material.

[0068] Step 6: Ethanol Gas Sensing Test

[0069] After sealing the detection chamber, sufficient N2 was introduced until the baseline resistance was stable. Then, ethanol gas with different concentrations (0.1-10 ppm) was introduced, and the resistance response changing with the gas content was observed.

[0070] Example 2

[0071] Step 1: Prepare the mixture:

[0072] 0.030 mmol of nickel nitrate hexahydrate (Ni(NO3)2·6H2O) was added to 5.5 mL of ethanol and ultrasonically treated to obtain a nickel nitrate solution. 0.019 mmol of HITP·6HCl was then dissolved in 5 mL of ethanol and ultrasonically treated to obtain a HITP·6HCl solution. Subsequently, 0.4 mL of concentrated ammonia solution (NH3·H2O) and the obtained nickel nitrate solution were added dropwise to the HITP·6HCl solution to obtain a mixed solution.

[0073] Step 2: Preparation of Ni3(HITP)2 / MXene nanosheets

[0074] 4 mL of MXene nanosheet dispersion was added to the mixed solution prepared in step 1, and the mixed solution was subjected to water bath sonication. After the sonication, the mixed solution was placed in a reactor for heating reaction, wherein the oven heating temperature was 60°C and the heating time was 5 h. After the reaction, the obtained black suspension was centrifuged and washed, wherein the centrifugal speed was 9000 r / min and the centrifugal time was about 2 min. At the same time, the centrifugal washing operation was performed at least 6 times;

[0075] Furthermore, the washed black suspension is dried under vacuum at 150°C to obtain Ni3(HITP)2 / MXene, or ethanol is added to the washed black suspension to prepare a Ni3(HITP)2 / MXene nanosheet dispersion with a certain concentration.

[0076] Step 3: Device Pretreatment

[0077] The sensor device printed with interdigital electrodes was immersed in ethanol for 2 days to fully remove impurities on the surface of the sensor device, and then vacuum dried at 60° C. for 10 hours.

[0078] Step 4: Prepare the sensing layer

[0079] The prepared Ni3(HITP)2 / MXene dispersion was evenly spin-coated or drop-coated on the surface of the sensor printed with interdigital electrodes. The entire sensor was then heated and dried at 80°C. After it was completely dry, a gas sensing test was performed, and the thickness of the entire sensing layer was controlled at 250nm.

[0080] Step 5: Sensor Assembly

[0081] The test electrodes of the sensor prepared by the above steps are connected to the electrode columns located at the octagonal base of the detection cavity, thereby obtaining an ethanol gas sensor with Ni3(HITP)2 / MXene as the sensitive material.

[0082] Step 6: Ethanol Gas Sensing Test

[0083] After sealing the detection chamber, sufficient N2 was introduced until the baseline resistance was stable. Then, ethanol gas with different concentrations (0.1-10 ppm) was introduced, and the resistance response changing with the gas content was observed.

[0084] Example 3

[0085] Step 1: Prepare the mixture:

[0086] 0.032 mmol of nickel nitrate hexahydrate (Ni(NO3)2·6H2O) was added to 6 mL of ethanol and ultrasonically treated to obtain a nickel nitrate solution. 0.022 mmol of HITP·6HCl was then dissolved in 6 mL of ethanol and ultrasonically treated to obtain a HITP·6HCl solution. Subsequently, 0.5 mL of concentrated ammonia solution (NH3·H2O) and the obtained nickel nitrate solution were added dropwise to the HITP·6HCl solution to obtain a mixed solution.

[0087] Step 2: Preparation of Ni3(HITP)2 / MXene nanosheets: 5 mL of MXene nanosheet dispersion was added to the mixed solution prepared in step 1, and the mixed solution was subjected to water bath sonication. After the sonication, the mixed solution was placed in a reactor for heating reaction, wherein the oven heating temperature was 65°C and the heating time was 6 hours. After the reaction, the obtained black suspension was centrifuged and washed, wherein the centrifugal speed was 10000 r / min, the centrifugal time was about 3 minutes, and the centrifugal washing operation was performed at least 7 times;

[0088] Furthermore, the washed black suspension is dried under vacuum at 150°C to obtain Ni3(HITP)2 / MXene, or ethanol is added to the washed black suspension to prepare a Ni3(HITP)2 / MXene dispersion with a certain concentration.

[0089] Step 3: Device Pretreatment

[0090] The sensor device printed with interdigital electrodes was immersed in ethanol for 2 days to fully remove impurities on the surface of the sensor device, and then vacuum dried at 60° C. for 10 hours.

[0091] Step 4: Prepare the sensing layer

[0092] The prepared Ni3(HITP)2 / MXene dispersion was evenly spin-coated or drop-coated on the surface of the sensor printed with interdigital electrodes. The entire sensor was then heated and dried at 80°C. After it was completely dry, a gas sensing test was performed, and the thickness of the entire sensing layer was controlled at 450nm.

[0093] Step 5: Sensor Assembly

[0094] The test electrodes of the sensor prepared by the above steps are connected to the electrode columns located at the octagonal base of the detection cavity, thereby obtaining an ethanol gas sensor with Ni3(HITP)2 / MXene as the sensitive material.

[0095] Step 6: Ethanol Gas Sensing Test

[0096] After sealing the detection chamber, sufficient N2 was introduced until the baseline resistance was stable. Then, ethanol gas with different concentrations (0.1-10 ppm) was introduced, and the resistance response changing with the gas content was observed.

[0097] Comparative Example 1

[0098] Step 1: Prepare the mixture:

[0099] 0.028 mmol of nickel nitrate hexahydrate (Ni(NO3)2·6H2O) was added to 5 mL of ethanol and ultrasonically treated to obtain a nickel nitrate solution. 0.020 mmol of HITP·6HCl was then dissolved in 5 mL of ethanol and ultrasonically treated to obtain a HITP·6HCl solution. Subsequently, 0.3 mL of concentrated ammonia solution (NH3·H2O) and the obtained nickel nitrate solution were added dropwise to the HITP·6HCl solution to obtain a mixed solution.

[0100] Step 2: Preparation of Ni3(HITP)2

[0101] The mixed solution obtained in step (1) was subjected to water bath sonication. After the sonication, the mixed solution was placed in a reactor for heating reaction, wherein the oven heating temperature was 55° C. and the heating time was 4 h. After the reaction, the obtained black suspension was centrifuged and washed, wherein the centrifugal speed was 8000 r / min, the centrifugal time was about 1 min, and the number of centrifugal washings was 5 times;

[0102] Furthermore, the washed black suspension is dried under vacuum at 150° C. to obtain Ni 3 (HITP) 2 , or ethanol is added dropwise to the washed black suspension to prepare a Ni 3 (HITP) 2 dispersion with a certain concentration.

[0103] Step 3: Device Pretreatment

[0104] The sensor device printed with interdigital electrodes was immersed in ethanol for 1 day to fully remove impurities on the surface of the sensor device, and then heated to 80°C for drying.

[0105] Step 4: Prepare the sensing layer

[0106] The prepared Ni3(HITP)2 dispersion was evenly spin-coated or drop-coated on the surface of the sensor printed with interdigital electrodes. The entire sensor was then heated and dried at 80°C. After it was completely dried, a gas sensing test was performed, and the thickness of the entire sensing layer was controlled at 300nm.

[0107] Step 5: Sensor Assembly

[0108] The test electrodes of the sensor prepared by the above steps are connected to the electrode columns located at the octagonal base of the detection cavity, thereby obtaining an ethanol gas sensor using Ni3(HITP)2 as the sensitive material.

[0109] Furthermore, the octagonal base is used to connect the sensor substrate and the test cavity. More preferably, the octagonal base is a plastic structure with 8 electrode columns evenly distributed, and the heating electrode and test electrode of the sensor substrate will be welded to 4 specific electrode columns respectively.

[0110] Step 6: Ethanol Gas Sensing Test

[0111] After sealing the detection chamber, sufficient N2 was introduced until the baseline resistance was stable. Then, ethanol gas with different concentrations (1-10 ppm) was introduced, and the resistance response was observed as the gas content changed.

[0112] Compare Comparative Example 1 with Example 1:

[0113] Morphological and structural characterization of Ni3(HITP)2 and Ni3(HITP)2 / MXene

[0114] Morphological characterization

[0115] 1 mL of each dispersion of the Ni3(HITP)2 and Ni3(HITP)2 / MXene nanomaterials prepared in Example 1 was added to a centrifuge tube, diluted with 5 mL of ethanol, and 6 μL of each was dropped onto a silicon wafer and observed under a scanning electron microscope. Then, 1 mL of each dispersion of the Ni3(HITP)2 and Ni3(HITP)2 / MXene nanomaterials prepared in Example 1 was added to a centrifuge tube, diluted with 10 mL of ethanol, and 10 μL of each was dropped onto a silicon wafer and a copper mesh, and observed under an atomic force microscope and a transmission electron microscope.

[0116] like Figure 1As shown in (ab), from the scanning electron microscope (SEM) photos, it can be seen that the morphology of Ni3(HITP)2 is porous and loose, and the overall particles are clustered together, with no fixed shape and no regular arrangement behavior. The morphology of Ni3(HITP)2 / MXene is that Ni3(HITP)2 grows uniformly on the surface of two-dimensional MXene nanosheets, forming a Ni3(HITP)2 / MXene nanosheet structure. Figure 1 As shown in (cd), it can be seen from the atomic force microscopy (AFM) photos that the thickness of the bottom template MXene nanosheet in the Ni3(HITP)2 / MXene nanomaterial is about 4nm, while the thickness of the Ni3(HITP)2 layer is about 6-10nm.

[0117] like Figure 2 As shown in (ab), the nanosheet structure of Ni3(HITP)2 / MXene can be seen from the transmission electron microscopy (TEM) images. The lattice spacing of Ni3(HITP)2 on the Ni3(HITP)2 / MXene nanosheets was measured by high-resolution transmission electron microscopy (HR-TEM) to be approximately 2.1 nm, corresponding to the (100) interplanar spacing of Ni3(HITP)2 crystals. Figure 2 As shown in (ce), the elemental distribution map clearly shows the presence of Ni and Nb, the characteristic elements in Ni3(HITP)2 and MXene nanosheets. The elemental distribution map clearly shows the presence of Ni and Nb elements, indicating the successful synthesis of Ni3(HITP)2 / MXene nanosheets.

[0118] Structural characterization

[0119] 5 mg each of the Ni3(HITP)2 and Ni3(HITP)2 / MXene nanomaterials prepared in Example 1 were taken for XRD testing. Then, 50 mg each of the Ni3(HITP)2 and Ni3(HITP)2 / MXene nanomaterials prepared in Example 1 were taken for powder resistivity testing using the four-probe method.

[0120] like Figure 3 As shown in the figure, Ni3(HITP)2 and Ni3(HITP)2 / MXene nanosheets both exhibit similar characteristic peaks in the XRD patterns, indicating that after Ni3(HITP)2 is grown on the surface of two-dimensional MXene nanosheets, it still maintains relatively good crystallinity. At the same time, the appearance of multi-order diffraction peaks

[100] and

[200] proves that the long-range order in the ab plane is good, and the weaker and broader peak at

[001] indicates that the long-range order along the c direction is poor, which is also consistent with the structural expectations of two-dimensional materials.

[0121] like Figure 4As shown in the figure, the resistivity curves of Ni3(HITP)2 and Ni3(HITP)2 / MXene nanosheets decrease with increasing pressure and finally tend to be stable. The corresponding conductivity curves increase with increasing pressure and finally tend to be stable. The results show that the stable resistivity of Ni3(HITP)2 is about 0.369Ω·cm, and the corresponding stable conductivity is about 2.7S / cm, while the stable resistivity of Ni3(HITP)2 / MXene nanosheets is about 0.02Ω·cm, and the corresponding stable conductivity is about 48.3S / cm. Compared with Ni3(HITP)2, the conductivity of MXene in the Ni3(HITP)2 / MXene nanosheet system is between 10-100S / cm, which makes the conductivity of Ni3(HITP)2 / MXene nanosheets significantly improved compared with Ni3(HITP)2, and can effectively enhance its gas sensing performance.

[0122] Solution processability of Ni3(HITP)2 / MXene

[0123] The Ni3(HITP)2 / MXene dispersion prepared in Example 1 was diluted with 2 mL of ethanol and dropped onto a substrate made of polyvinylidene fluoride (PVDF). A large-area thin film was prepared using a doctor blade.

[0124] The large-area thin film prepared by the doctor blade is about 23 cm long and 9 cm wide. The preparation of the uniform and dense large-area thin film shows that the Ni3(HITP)2 / MXene system has good solution processing ability, which further reduces the difficulty of traditional MOF materials in device preparation and significantly simplifies the film-making process of MOF materials as the sensing layer in gas sensor devices. The good solution processing ability provides the possibility for the large-scale preparation of gas sensor devices based on MOF materials.

[0125] Sensing performance of gas sensors based on Ni3(HITP)2 / MXene

[0126] The Ni3(HITP)2 and Ni3(HITP)2 / MXene nanosheet dispersions prepared in Example 1 were evenly spin-coated or drop-coated on the surface of the sensor printed with interdigital electrodes. The entire sensor was then heated and dried at 80°C. After it was completely dried, a gas sensing test was performed.

[0127] The specific gas detection process is as follows: first, the test electrodes of the prepared sensor are connected to the electrode columns of the octagonal base located in the detection chamber, and a gas sensor with Ni3(HITP)2 / MXene as the sensitive material is obtained.

[0128] After sealing the detection chamber, introduce sufficient N2 until the baseline resistance stabilizes, then introduce gases of different types and concentrations, and then observe and record the resistance response that changes with gas content.

[0129] Ethanol gas sensor test

[0130] like Figure 5 As shown in (ac), after ethanol gas with a concentration of 1-10ppm was passed into the detection chamber, obvious resistance response changes were observed in both Ni3(HITP)2 and Ni3(HITP)2 / MXene systems, and the resistance change of the Ni3(HITP)2 / MXene system was about 4 times higher than that of the Ni3(HITP)2 system, indicating that the Ni3(HITP)2 system has higher sensitivity to ethanol gas. At the same time, ethanol gas with a concentration of 0.1-1.5ppm was tested, and it was observed that the resistance response change of the Ni3(HITP)2 / MXene system to ethanol gas with a concentration of 100ppb was about 0.28%, which has a lower detection limit than all current MOF-based ethanol gas sensors.

[0131] Gas selectivity test

[0132] After introducing five different types of gases, including ethanol, ammonia, acetone, formaldehyde, and carbon monoxide, with a concentration of 10 ppm, into the detection chamber, the selective response of Ni3(HITP)2 and Ni3(HITP)2 / MXene nanosheets to different gases was tested. The test results are shown in Figure 2. Figure 6 As shown in the figure, obvious resistance response changes were observed for Ni3(HITP)2 and Ni3(HITP)2 / MXene systems to five different types of gases, and both showed higher resistance changes to ethanol. Compared with Ni3(HITP)2, Ni3(HITP)2 / MXene system has better selectivity for ethanol, with the maximum resistance change of about 28.8%, which is significantly higher than the resistance response changes of the other four gases. This indicates that the synergistic effect of the heterojunction between Ni3(HITP)2 / MXene potentially improves the gas-sensitive selectivity for ethanol gas.

[0133] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.

Claims

1. A method for preparing a Ni3(HITP)2 / MXene heterostructure, characterized in that: The following steps are involved: S1: dissolving HITP·6HCl in ethanol to obtain a HITP·6HCl solution, and then adding concentrated ammonia water and nickel nitrate solution to the HITP·6HCl solution to obtain a mixed solution; S2: adding MXene nanosheet dispersion to the mixed solution, and then subjecting the mixed solution to ultrasonication, heating, and in-situ growth to obtain a Ni3(HITP)2 / MXene composite nanosheet suspension; In the step S1, the preparation of the nickel nitrate solution comprises adding nickel nitrate hexahydrate to ethanol and obtaining the nickel nitrate solution after ultrasonic treatment; In the step S2, the heating temperature is 55-65°C and the heating time is 4-6 hours.

2. A method for preparing a Ni3(HITP)2 / MXene heterostructure according to claim 1, characterized in that: In the step S1, the molar ratio of the nickel nitrate solution to the HITP·6HCl solution is (3-2): (3.5-2).

3. A method for preparing a Ni3(HITP)2 / MXene heterostructure according to claim 2, characterized in that: In step S1, the amount of concentrated ammonia solution used is 0.3-0.5 mL.

4. The method for preparing a Ni3(HITP)2 / MXene heterostructure according to claim 1, characterized in that: In the step S1, the usage ratio of the nickel nitrate hexahydrate to ethanol is 0.028-0.032 mmol: 5-6 mL.

5. A method for preparing a Ni3(HITP)2 / MXene heterostructure according to claim 4, characterized in that: In the step S1, the usage ratio of HITP·6HCl to ethanol is 0.019-0.022 mmol: 5-6 mL.

6. The method for preparing a Ni3(HITP)2 / MXene heterostructure according to claim 1, characterized in that: The step S2 further includes centrifuging the heated solution for 1-3 min; After centrifugation, the solution is washed for 5 or more times.

7. An ethanol gas sensor, characterized in that: It comprises the Ni3(HITP)2 / MXene composite nanosheet suspension as claimed in claim 1, wherein the Ni3(HITP)2 / MXene composite nanosheet suspension is loaded on the surface of the sensor.

8. An ethanol gas sensor according to claim 7, characterized in that: The thickness of the Ni3(HITP)2 / MXene layer is 220-450 nm.

Citation Information

Patent Citations

  • KR20220032312A